Xenon-induced effects in relieving experimental acute respiratory distress syndrome - Fedorova, E. P.; Filonova, Mariya V.; Churin, Alexey A.; Naumov, Sergei Alexandrovich; Nikiforov, P. E.; Sandrikina, Lyubov A.; Evtushenko, Diana Nikolaevna; Udut, Elena V.; Popov, O. V.; Naumov, Sergei Sergeevich; Fomina, Tatyana I.; Udut, Vladimir V. (Bulletin of experimental biology and medicine)
The effects of inhalations of an oxygen-xenon (70%/30%) mixture were studied in two models of acute respiratory distress syndrome caused by intratracheal administration of 0.5 mg/kg LPS or 0.04 ml acidin-pepsin (pH 1.2). Inhalation of the oxygen-xenon mixture inhibited the development and reduced the intensity of the inflammatory process in the lung tissue, which was assessed by the dynamics of lung weight and body weight of animals: the therapeutic exposure decreased both parameters. It was found that the thrombogenic stimulus, pathognomonic for the development of acute respiratory distress syndrome, decreased under the effect of oxygen-xenon inhalations, while the level of natural anticoagulant antithrombin III increased.